Models of Experimental Sporotrichosis and Immune Response Against Sporothrix schenckii - Carlos, Iracilda Zeppone [UNESP]; Ferreira, Lucas Souza [UNESP]; Gonçalves, Amanda Costa [UNESP] (Springer Nature, 2015)
Antifungal host responses can vary depending on the site of infection, fungal pathogen, fungal morphotype (yeast versus hyphae), and immune status of the host. Variation in the virulence of individual Sporothrix schenckii strains and the immune status of the host may both contribute to the variety in the clinical manifestations of sporotrichosis. However, the factors involved in the pathogenesis of sporotrichosis and the mechanisms determining S. schenckii virulence remain unclear. Classic murine models of sporotrichosis display a characteristic transitory state of depressed cell–mediated immunity during the disease's acute phase, which has been suggested to result from the nitric oxide–induced T–cell apoptosis and loss of responsiveness to mitogens. In sporotrichosis, recognition of the S. schenckii lipid components, through Toll–like receptor (TLR)–4 or via an inflammasomedependent pathway, seems to drive inflammation, whereas the TLR2–mediated recognition of the fungus's exoantigen may serve as an escape mechanism, although the S. schenckii internalization by TLR2¯/¯ macrophages is almost completely abrogated, in vitro at least. Finally, both in vitro and in vivo studies have suggested the adaptive immune response against S. schenckii to be of a mixed Th1/Th17 pattern, with a predominance of Th17 and Th1/Th17 mixed cells over Th1 cells. In this chapter we discuss the current understanding of the immune mechanisms triggered by S. schenckii sensu strictu, along with the animal models used so far to study this pathogen.
Keywords: Animal model; Cytokines; Sporothrix schenckii; Th17 cells